1962
DOI: 10.1136/gut.3.4.306
|View full text |Cite
|
Sign up to set email alerts
|

The management of fulminant ulcerative colitis

Abstract: EDITORIAL SYNOPSIS This paper describes the management of 23 patients with fulminant ulcerative colitis, 22 of whom had early surgery when medical treatment was unsuccessful. There were two deaths, a mortality of 9 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1963
1963
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…If results are to be improved, surgery must come sooner. This accounted for the better results obtained by Gallagher, Goulston, Wyndham, and Morrow (1962), who had two deaths in their series of 23 patients. The absence of perforation in their series encouraged them to adhere to this policy of early surgery.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…If results are to be improved, surgery must come sooner. This accounted for the better results obtained by Gallagher, Goulston, Wyndham, and Morrow (1962), who had two deaths in their series of 23 patients. The absence of perforation in their series encouraged them to adhere to this policy of early surgery.…”
Section: Discussionmentioning
confidence: 86%
“…The phenomenon of colonic dilatation has aroused considerable interest and comment as to its aetiology. Some suggest that it is caused by hypokalaemia (Cohn, Copit and Turner, 1956), or the destruction of the autonomic nerve plexuses in the bowel wall (Bockus, Roth, Buchman, and Kalser, 1958), or smooth muscle toxic destruction (Walker and Curtis, 1965), although as Gallagher et al (1962) have pointed out, and in the present series this is confirmed, often the dilatation of the colon is most evident in areas that are not so grossly diseased, as in the right-sided colonic dilatation where there is advanced disease principally on the left side.…”
Section: Discussionmentioning
confidence: 99%
“…Their assumption is that emergency surgery would be less hazardous if performed earlier in the course of the illness than was usual in their cases. This view is strongly pressed by Gallagher, Goulston, Wyndham, and Morrow (1962) who claim that their overall results for severe ulcerative colitis have improved since they adopted the policy of early operation after a short period of intensive treatment usually lasting one to three weeks; among 22 patients so treated, there were only two deaths (91 %).…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach would involve a short course of intensive medical treatment, which, unless an immediate response occurs, is followed by early radical surgery, as practised so successfully by Gallagher, Goulston, Wyndham, and Morrow (1962) in a younger group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, realization of the hazards of emergency operation encourages the clinician to persist with conservative measures as long as possible; on the other hand, it could be said that, if operation were undertaken much earlier before the patient's general condition had deteriorated significantly, at least some of the hazards of surgery might be obviated. Such early intervention has been practiced by Gallagher et al (1962) with reduction of their operative mortality to 9% in 'fulminating' cases. In the light of our results, we propose to give a thorough trial to this policy of invoking surgical aid at a very early stage of severe attacks, unless there is unequivocal evidence of rapid improvement on medical treatment.…”
Section: Course Of the Disease After The First Attackmentioning
confidence: 99%